Sosialisasi Pengelolaan Dana Desa di Gampong Ujong Drien Kecamatan Meureubo Kabupaten Aceh Barat - Jerri Gunandar; Sopar Sopar; Arfriani Maifizar (Universitas Teuku Umar, 2021)
The socialization of village fund management in Ujong Drien Village aims to increase the knowledge of village officials about village fund management accounting, so that village officials can make plans, implement programs and activities, which are funded by APBG, and are able to make transparent and accountable village financial reports. This service activity was carried out at the office of the village head Ujong Drien which was attended by 13 participants consisting of the village head, village secretary, and village officials. This service activity runs smoothly according to plan. Meanwhile, the method used in this service activity is to conduct socialization and discussion related to village fund management material. The result of this activity is that the participants know more about village fund management, especially about accounting which leads to transparent and accountable village financial reporting.